(untitled) (ENTHYMEMA, 2019)
The aim of the article is to ponder, from a narratological perspective, on the fictional pacts in William T. Vollmann’s Seven Dreamsseries, i.e., on the virtual contract through which the author gives the reader, whether explicitly or not, instructions about the way in which his texts should be read, and that the reader, in turn, should follow to coherently process textual contents. By focusing on The Ice-Shirt, the first novel in the series, I will try to demonstrate how such a pact proves to be a problematic one, especially in that, throughout the whole text, fictional and non-fictional elements are constantly blended. Moreover, my aim is to address how on the reader’s part a ‘flexible’ approach, i.e., an approach that recognizes and builds on such a compresence of elements, allows him to navigate a text that reveals to be hybrid in nature.